Relevansi Faktor Penegakan Hukum Menurut Soerjono Soekanto Dalam Menghadapi Fenomena Cyber Crime - Rima Fadhilatunnisa; Ahmad Rama; Antonia Alda Resalda; Muhammad Sulthon Robani Thai'ib; Rima Yuni Saputri; Dian Permata Sari (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2026)
The main challenge is the legal character, which often struggles to keep up with technological developments, and the failure in handling cyber crime is caused by a lack of balance among the five law enforcement factors of Soerjono Soekanto. This study aims to systematically describe the law enforcement factors according to Soerjono Soekanto. The research method used is a qualitative approach with a type of normative juridical research. This study shows that the development of information technology has brought significant changes in crime patterns, with cyber crime experiencing rapid growth in Indonesia. Therefore, education and the instilling of digital ethical values are needed to build intrinsic collective awareness, so that society is not only the object of protection but also an active subject in creating a safe and orderly digital space.